Effect of physical intimate partner violence on body mass index in low-income adult women - Marcela de Freitas Ferreira; Claudia Leite de Moraes; Michael Eduardo Reichenheim; Eliseu Verly Junior; Emanuele Souza Marques; Rosana Salles-Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
This study aimed to assess whether physical intimate partner violence affects the nutritional status of adult women with different levels of body mass index (BMI). This was a population-based cross-sectional study with 625 women selected through complex multistage cluster sampling. Information on physical intimate partner violence was obtained with the Revised Conflict Tactics Scales, and nutritional status was measured as BMI (kg/m2). A quantile regression model was used to assess the effect of physical intimate partner violence at all percentiles of BMI distribution. Physical intimate partner violence occurred in 27.6% of the women (95%CI: 20.0; 35.2). Mean BMI was 27.9kg/m2 (95%CI: 27.1; 28.7). The results showed that physical intimate partner violence was negatively associated with BMI between the 25th and 85th percentiles, corresponding to 22.9 and 31.2kg/m2. The findings support previous studies indicating that physical intimate partner violence can reduce BMI in low-income women.